Development and application of a whole transcriptome sequencing assay for the detection of gene fusions in clinical cancer specimens - Songchen Zhao; Xinhua Du; Yan Zhang; Jing Bai; Lu Meng; Xuefei Li; Jiaxin Ma; HeYu Sheng; Xiaorui Fu; Yanfang Guan; Yuting Yi; Ling Yang; et al. (BMC Cancer)
Abstract Background Gene fusions are an important driver of cancer and require rapid and accurate detection to guide clinical decisions. However, the performance characteristics of whole transcriptome sequencing (WTS) for the detection of gene fusions have not been thoroughly investigated. Methods We developed a novel WTS-based assay for the detection of gene fusions, MET exon 14 skipping and EGFR VIII alterations in clinical samples. Results We defined a DV200 value ≥ 30% as the threshold for RNA degradation, RNA input, fusion expression and number of mapped reads greater than 100 ng, 40 copies/ng and 80 Mb for optimal sensitivity of the WTS assay. Our assay successfully identified 62 out of 63 known gene fusions, achieving a sensitivity of 98.4%. The specificity of the assay was 100%, as no fusions were detected in the 21 fusion-negative samples. Good repeatability and reproducibility were observed in replicates, except for the TPM3::NTRK1 fusion, which was expressed below the threshold. Of all fusions identified in 101 NSCLC samples, 68.9% (20/29) were potentially actionable, compared to 20% in pan-cancer samples. In addition to actionable fusions, we also identified many fusions with potential diagnostic and prognostic value in pan-cancer. Conclusions We have developed a novel WTS assay with high sensitivity, specificity, repeatability and reproducibility. This assay can identify potentially actionable gene fusions and provides valuable insights into the fusion landscape in various cancers, which may help guide treatment decisions and aid in diagnosis and prognosis.